ANALYSIS OF THE EFFICIENCY OF IMPLEMENTING THE PUBLIC BUDGET STRATEGY AND ITS ALIGNMENT WITH THE ANNUAL GOVERNMENT PROGRAM OBJECTIVES: A CASE STUDY OF IRAQ AND JORDAN - Zinah saad hasan al-musawi (Scholar Express Journals, 2024)
To achieve the objectives of annual government programs, a strategy must be available for those programs that is consistent with their available financial capabilities and what they aspire to achieve in the near future. Thus, that strategy should be supported and endorsed by the technical and supervisory bodies with decision-making powers in the countries sampled by the research. The research has concluded that this The authorities were characterized by their support of the executive authority to achieve the goals of its government program, but due to their weak performance in implementing their financial program that was approved and which they must implement and exploit resources to achieve the goals of that program, this prevented them from achieving the desired goal, for which the appropriate amount of expenditures were planned and estimated based on the value of the index. Efficiency of achieving the goal in the countries of the research sample. The research recommended that it is necessary to work on adopting types of budgets with high efficiency and the ability to implement quickly, especially in Iraq, such as program and performance budgets and disposal budgets. We must gradually shift from relying on traditional line item budgeting
Keywords: Budget Strategy; Efficiency of Government Spending; Evolution of Government Spending